A drastic change in the superhydrophilic crystal porosities of metallosupramolecular structures via a slight change in pH. Issue 87 (14th October 2016) - Surinwong, Sireenart; Yoshinari, Nobuto; Kojima, Tatsuhiro; Konno, Takumi
Abstract : Unique non-porous and porous metallosupramolecular frameworks are created fromd -penicillaminato CoIII2AuI3 complex anions and zinc(ii ) cations. Abstract : A unique pH-controlled synthesis of two metallosupramolecular structures from CoIII2AuI3 complex anions and Zn II cations is reported. A dense coordination polymer (porosity ∼13%) was formed at a pH of 5.0, whereas a porous ionic framework (porosity ∼61%) that selectively adsorbs CO2 and H2 O was created when the pH was adjusted to 5.5.